SPIRITUAL AND MORAL EDUCATION OF STUDENTS THROUGH FOLK SONGS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article is about the spiritual and moral education of students through folk songs. Music is an art by nature. Organizing it in a colorful, meaningful and interesting way requires great pedagogical and professional skills of each teacher.